Research trends in Rift Valley fever virus: a bibliometric analysis from 1936 to 2024 - Zhang, Huiying; Song, Shuai; Zhang, Leiliang (Frontiers in Veterinary Science, 2025)
BackgroundRift Valley fever (RVF), first identified in Kenya in 1930, is a viral zoonosis transmitted by arthropods and poses significant risks to both public and animal health. Despite the wealth of published studies on the disease, the number of bibliometric analysis of Rift Valley fever virus (RVFV) is limited. This study utilized bibliometric analysis to identify research hotspots and emerging trends in RVFV studies, aiming to offer new insights and strategic references for future research directions and prevention strategies.MethodsThe study utilized Scopus to collect global publications on RVFV from 1936 to 2024. Data processing and visualization were performed with VOSviewer, CiteSpace, Scimago Graphica, and the Bibliometrix web tool.ResultsA total of 1,629 publications related to RVFV were included in this analysis. Geographic distribution showed that the United States, France, and Kenya were the most productive countries in this field, while Institut Pasteur emerged as the leading research institution. PLoS Neglected Tropical Diseases was identified as the predominant journal for publishing RVFV research, while Virology received the highest citation frequency. Author analysis revealed Clarence Peters as the most prolific contributor, with “Rift Valley fever virus” being the most frequently used keyword.ConclusionThis bibliometric investigation systematically assessed nine decades of research on RVFV, providing a comprehensive overview of the contributions from leading nations, institutions, researchers, and journals in this field. Global interest in RVFV research has been steadily increasing, particularly in recent years. This surge in attention, largely influenced by climate change, has attracted heightened focus from public health departments.